Genetic structure of the endangered milky stork (Mycteria cinerea) in Thailand with implications for captive breeding and reintroduction - Amporn Wiwegweaw; Damisa Kaminsin; Chitchai Chantangsi; Natapot Warrit; Nutthanun Khantasup; Saowaphang Sanannu; Wirongrong Changphet (Scientific Reports)
Abstract Local extinction of milky stork Mycteria cinerea has been reported from the wild of Thailand. Only one captive population exists at Nakhon Ratchasima Zoo and is currently maintained as a breeding stock of the country. To initiate future reintroduction program, determination of genetic diversity in this captive population is crucial for its long-term sustainability in nature. The present study employed a combination of maternally inherited mitochondrial control region and biparentally inherited nuclear microsatellite markers to evaluate genetic status of these captive individuals. Phylogenetic analysis and haplotype network construction demonstrated moderate haplotype diversity (h = 0.560 ± 0.050) and low nucleotide polymorphism (π = 0.0007 ± 0.0001). Multilocus microsatellite examination further showed low heterozygosity (H O = 0.387; H E = 0.374) with no significant evidence of inbreeding (F IS = -0.036). Moreover, STRUCTURE computation revealed two distinct genetic clusters among all studied individuals. Cluster 1 carried all three identified haplotypes and exhibited relatively higher genetic diversity than the cluster 2. Significant inbreeding was not observed in these two clusters. Assessment of pairwise relatedness additionally indicated that a majority of sample pairs were not genealogically related, thereby providing potential candidates for future breeding. Finally, suitable stork individuals and criteria for the effective selection of breeding pairs are proposed. Our research not only reports comprehensive genetic data of the sole remaining population of Thai milky stork for the first time, but also proposes a practical strategic framework by utilizing the obtained genetic information along with judicious breeding selection for recovering this endangered species of Thailand.